Nurse’s activities in the prevention of phlebitis caused by medicines (Research, Society and Development, 2020)
Objective: describe the nurse`s team care in the prevention and treatment of the complications in peripheric venous puncture in patients in the ICU. Method: the methodology used was descriptive, carried out through a bibliographic review published in the period from 2008 to 2019, whose survey was performed in a virtual environment in the Virtual Health Library (VHL), on the bases: Medline and Lilacs. Results: phlebitis can be prevented by performing aseptic technique during insertion of the venous device and adopting suitable material of appropriate size for vein caliber, preferably of small caliber, which is flexible with high resistance to bending, structural integrity, easy insertion, low thrombogenicity and bacterial adherence. Conclusion: it was possible to identify that the ducts are very similar in different services and that most care are common nursing procedures and have proven efficacy through scientific studies.